2017
DOI: 10.21448/ijsm.376942
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Health Services Vocational School Students’ Thoughts and Usage Habits about Herbal Treatment

Abstract: Usage of complementary-alternative medicine (CAM) is increasing in a rapid manner. Among CAM, herbal applications come in the foreground. This cross-sectional study was conducted by using 'questionnaire application method' on 342 students in Inonu University Health Services Vocational School. Analyzes of the data was made by SPSS 17.0 programme by using frequency, percentage and q-square tests. According to the data, 44.1% of the students were obtained to use herbal treatment. Among students; 70,0% stated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
3
0
3
Order By: Relevance
“…çalışmasında öğrencilerin %44,1'i alternatif tedavi kullandığını, %31,3'ü bitkisel ürünleri vücudu ve bağışıklık sistemini güçlendirmek için kullandığını, %40,9'u bitkisel ürünleri aktardan aldıklarını, %32,5'i bitkisel ürünleri şikayetlerini azaltmak için kullandıklarını, %21,3'ü bitkilerin ilaçlardan daha güvenli olduğunu ve %13,0'ı yan etki geliştiğini belirtmişlerdir. 20 Tulukcu ve Sağdıç'ın çalışmasında Konya'daki aktarlarda satışa sunulan bitkilerin yaprak, tohum ve meyve gibi bitki yapılarından meydana geldiği ve tedavi amacıyla bitkilerin yaprak, gövde, kök, çiçek, tohum ve filiz gibi kısımlarını suyla kaynatma, kaynatılmış suya ekleme, yağın içerisinde bekletme, lapa olarak ya da balla hazırlanmış karışımlar şeklinde kullanıldığı belirlenmiştir. 15 Kaner ve ark.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…çalışmasında öğrencilerin %44,1'i alternatif tedavi kullandığını, %31,3'ü bitkisel ürünleri vücudu ve bağışıklık sistemini güçlendirmek için kullandığını, %40,9'u bitkisel ürünleri aktardan aldıklarını, %32,5'i bitkisel ürünleri şikayetlerini azaltmak için kullandıklarını, %21,3'ü bitkilerin ilaçlardan daha güvenli olduğunu ve %13,0'ı yan etki geliştiğini belirtmişlerdir. 20 Tulukcu ve Sağdıç'ın çalışmasında Konya'daki aktarlarda satışa sunulan bitkilerin yaprak, tohum ve meyve gibi bitki yapılarından meydana geldiği ve tedavi amacıyla bitkilerin yaprak, gövde, kök, çiçek, tohum ve filiz gibi kısımlarını suyla kaynatma, kaynatılmış suya ekleme, yağın içerisinde bekletme, lapa olarak ya da balla hazırlanmış karışımlar şeklinde kullanıldığı belirlenmiştir. 15 Kaner ve ark.…”
Section: Discussionunclassified
“…çalışmasında da öğrencilerin bitkisel ürünlerle ilgili bilgi sahibi olma durumlarının yetersiz olduğu, bitkisel tedavi kullanım durumlarının öğrencilerin ekonomik durumları ile karşılaştırılmasında anlamlı bir fark olduğu ve ekonomik durumu orta ve kötü düzeyde olanların bitkisel tedavileri daha çok kullandıkları belirlenmiştir. 20 Özçelik ve ark. çalışmasında kadınların ve eğitim seviyesi yüksek olan bireylerin bitkisel ürünleri daha fazla kullandıkları belirlenmiştir.…”
Section: Discussionunclassified
“…In a study on university students performed by Dinçer et al (12), students were found to have, in general, a positive attitude towards the older people. In different studies conducted on nursing and elder care students, students were shown to generally have a positive attitude towards the older people (1,8,13). In a study written by Altay and Aydın (10), students exhibited a positive attitude towards older people discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Old age involves living with social relationships in a social environment. The boosted health problems with ageing increase the demand of the elderly population for healthcare services (1). Older people become sick more often, have to live with more chronic diseases or disorders, are challenged by multiple health problems at the same time and are, thus, more frequently admitted to healthcare centres and stay longer at the hospitals (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation